Dead Man Walking: An Empirical Reassessment of the Deterrent Effect of Capital Punishment Using the Bounds Testing Approach to Cointegration - Paresh Kumar Narayan
This paper empirically estimates a murder supply equation for the United States from 1965 to 2001 within a cointegration and error correction framework. Our findings suggest that any support for the deterrence hypothesis is sensitive to the inclusion of variables for the effect of guns and other crimes. In the long-run we find that real income and the conditional probability of receiving the death sentence are the main factors explaining variations in the homicide rate. In the short-run the aggravated assault rate and robbery rate are the most important determinants of the homicide raCapital Punishment, Deterrent Effect, Cointegration